2000
DOI: 10.1093/carcin/21.11.1925
|View full text |Cite
|
Sign up to set email alerts
|

Esterification of all-trans-retinol in normal human epithelial cell strains and carcinoma lines from oral cavity, skin and breast: reduced expression of lecithin:retinol acyltransferase in carcinoma lines

Abstract: When exogenous [(3)H]retinol (vitamin A) was added to culture medium, normal human epithelial cells from the oral cavity, skin, lung and breast took up and esterified essentially all of the [(3)H]retinol within a few hours. As shown by [(3)H]retinol pulse-chase experiments, normal epithelial cells then slowly hydrolyzed the [(3)H]retinyl esters to [(3)H]retinol, some of which was then oxidized to [(3)H]retinoic acid (RA) over a period of several days. In contrast, cultured normal human fibroblasts and human um… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 52 publications
6
85
0
Order By: Relevance
“…In addition, we showed that LRAT mRNA and protein decrease in TCC of the bladder with increasing pathological tumor stage. These data extend our previous research, which has shown that several types of human carcinomas, including breast, head and neck, skin, prostate, and kidney, exhibit major alterations in LRAT transcripts and a reduced ability to accumulate retinyl esters (25)(26)(27)(28)(29). We have also recently demonstrated differential LRAT protein expression in subtypes of renal cell carcinoma; specifically, LRAT expression was found to be higher in renal tumors, such as chromophobe renal cell carcinoma and renal oncocytoma, with an indolent biological behavior (30).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In addition, we showed that LRAT mRNA and protein decrease in TCC of the bladder with increasing pathological tumor stage. These data extend our previous research, which has shown that several types of human carcinomas, including breast, head and neck, skin, prostate, and kidney, exhibit major alterations in LRAT transcripts and a reduced ability to accumulate retinyl esters (25)(26)(27)(28)(29). We have also recently demonstrated differential LRAT protein expression in subtypes of renal cell carcinoma; specifically, LRAT expression was found to be higher in renal tumors, such as chromophobe renal cell carcinoma and renal oncocytoma, with an indolent biological behavior (30).…”
Section: Discussionsupporting
confidence: 89%
“…Two enzymes have been reported to catalyze retinyl ester synthesis, LRAT and acylCoA:ROL acyltransferase. LRAT levels are reduced in many types of carcinoma specimens and cell lines (25)(26)(27)(28)(29). Given the stated importance of retinyl esterification, then, it is likely that reduced expression of LRAT would result in reduced levels of RA, and thereby render the affected cells at least in part functionally retinoid deficient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, our conclusion does not exclude the possibility that, under some circumstances, CRAB-PII expression may be dissociated from RARa expression. A case in point is the ERa-negative MDA-MB-468 cell line, which expresses low RARa but high CRABPII mRNA levels (Guo et al, 2000). In human keratinocytes, RARg has been shown to drive CRABPII expression (Astrom et al, 1992;Di et al, 1998) suggesting that in MDA-MB-468 cells, which express RARg (Widschwendter et al, 1995), this receptor may account for CRABPII expression.…”
Section: Discussionmentioning
confidence: 99%
“…After the final wash, PBS was removed, and 0.5 ml of fresh PBS was added to each sample for harvesting. The retinoids were extracted from 350 l of organic phase from both the cell and medium samples of each sample in a dark environment as described (19,20). The HPLC was performed using a Waters Millennium system (Waters Corp., Milford, MA).…”
Section: The Cyp26a1mentioning
confidence: 99%